Analysis of Tax Avoidance Potential through Transfer Pricing Practices in Affiliated Transactions: A Case Study of PT MCA in 2021 - Kurnia, Randy; Lestari, Etty Puji; Diki (CV ODIS, 2025)
This study aims to analyze the potential for tax avoidance resulting from transfer pricing practices in affiliated transactions conducted by PT MCA in 2021. The method employed is a case study with a mixed-methods approach, combining qualitative and quantitative techniques. Data were obtained from financial statements, annual corporate income tax returns (SPT), and interviews. The analysis refers to the OECD Transfer Pricing Guidelines 2022, particularly using the Transactional Net Margin Method (TNMM) to assess the arm's length nature of the transactions. The results indicate indications of transfer pricing practices in PT MCA's affiliated transactions, which have led to a reduction in tax liabilities. This implies the potential for tax avoidance, measured through the Effective Tax Rate (ETR) ratio. The study provides significant implications for the Directorate General of Taxes in its oversight of transfer pricing practices that pose a risk to state revenue.